Large‐scale pest control in New Zealand beech forests. (27th September 2016) - Elliott, Graeme; Kemp, Josh
Summary: In 2014, baits laced with the poison sodium fluoroacetate (1080) were sown over 694 000 ha of mostly native beech forests in New Zealand to control rats, stoats and possums – a landscape‐scale pest control programme called 'Battle for our Birds'. This large pest control operation was necessitated by the mast seeding of beech trees which led to irruptions of rodent and stoats which were predicted to lead to decreases in vulnerable native wildlife. In this article, we describe why and how this extensive pest control programme was developed and implemented. We describe the seedfall monitoring that was used to determine the need for large‐scale rodent and stoat control and the response of these predators to this control. We also provide a summary of the bird monitoring that was undertaken to demonstrate the effectiveness or otherwise of the programme.